Density Functional Theory Investigation of the Interaction between Carbon Nanotubes and Water Molecules during Water Desalination Process - Loay Ahmed Elalfy Abdelhafiz (2012)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2012 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Nano- Science & Technology; Dissertation, Academic